KENDALI ARUS STARTING MOTOR INDUKSI SATU FASA MENGGUNAKAN MAGNETIC ENERGY RECOVERY SWITCH (MERS) - Ken Hasto; Muhammad Haddin; Dedi Nugroho (PSTE UNIMUS, 2015)
ABSTRACT Control of Electrical Energy at the induction motor starting can be done by adjusting the input Voltage so that the flow generated during the starting of the motor can be arranged magnitude. The purphose of this study was to determine the characteristic Magnetic Energi Recovery Switch(MERS), as the regulator of the input voltage at the time of induction motor starting so that the current can be controlled and can regulated the electrical energy consumed by the motor . The method does is to design the input voltage of the motor control by magnetic energy recovery switch MERS . Aplication MERS as a motor input voltage controller firstly be simulated with PSim Software, The simulated results, as a reference made prototype and tasted its feasibility, criteria feasible and not feasible Mers device can be determined, among others, large capacitance smaller than the capacitance resonance .maximum voltage capacitor is not more than twice the voltage source and has low harmonic impact Results Mers applications as controlling the input voltage at the beginning of starting an induction motor capable of improving lowers the voltage to 108 volts . Keywords : Device Mers, the energy regulator, power factor improvement